Synaptic modulation of glutamate in striatum of the YAC128 mouse model of Huntington disease - Judy Cheng; Ellen T. Koch; Daniel Ramandi; James P. Mackay; Timothy P. O’Leary; William Rees-Jones; Lynn A. Raymond (Neurobiology of Disease)
Background: Altered balance between striatal direct and indirect pathways contributes to early motor, cognitive and psychiatric symptoms in Huntington disease (HD). While degeneration of striatal D2-type dopamine receptor (D2)-expressing indirect pathway medium spiny neurons (iMSNs) occurs prior to that of D1-type dopamine receptor (D1)-expressing direct pathway neurons, altered corticostriatal synaptic function precedes degeneration. D2-mediated signaling on iMSNs reduces their excitability and promotes endocannabinoid (eCB) synthesis, suppressing glutamate release from cortical afferents. D2 receptors are also expressed on glutamatergic cortical terminals, cholinergic interneurons, and dopaminergic terminals from substantia nigra where they suppress release of glutamate, acetylcholine and dopamine, respectively, and these cell types may contribute to early striatal dysfunction in HD. Thus, we used corticostriatal brain slices and optogenetic probes to directly investigate neuromodulatory signaling in the transgenic YAC128 HD mouse model. Results: Low-dose D2 agonist quinpirole reduced cortically-evoked glutamate release in dorsal striatum of premanifest YAC128 slices but not WT, and blocking type 1 cannabinoid receptors mitigated this effect. YAC128 corticostriatal brain slices also showed increased evoked dopamine and reduced evoked eCB release compared to WT, while acetylcholine signaling patterns remained relatively intact. Conclusions: These findings suggest that YAC128 corticostriatal slices show increased D2 sensitivity that is eCB-dependent, and that dopamine and eCB release are altered at an early disease stage. We provide evidence for impaired neuromodulatory signaling in early HD, guiding therapeutic efforts prior to the onset of overt motor symptoms later on.